MENENTUKAN LOYALITAS PENGGUNA SHOPEEPAY BERDASARKAN USER EXPERIENCE DAN KEPERCAYAAN PELANGGAN - Hanif, Rifki (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to examine the effect of trust as a mediation between user experience on the loyalty of Shopeepay application users among students of the FEB Institute of Asia Malang. This study uses path analysis. The type of research used is explanatory research with survey methods—data obtained by distributing questionnaires to a sample of 40 student respondents obtained through purposive sampling. Regarding the analysed data, user experience affects user loyalty through consumer trust. At the same time, the user experience variable does not directly affect customer loyalty.